The Role of Litigation Risk in Shaping Valuation Techniques in Mergers and Acquisitions: A Qualitative Synthesis - Dadang Irawan; Chandra, Willy (LPPM STIE Kasih Bangsa, 2026)
This study explores how litigation risk influences valuation techniques in mergers and acquisitions (M&A), focusing on discounted cash flow (DCF) models and peer comparables. Through a qualitative synthesis of recent literature, it finds that legal exposure significantly alters valuation strategies—particularly in fairness opinions—prompting conservative estimates to mitigate shareholder lawsuits and regulatory scrutiny. The analysis reveals that litigation risk can distort valuation objectivity, reduce deal premiums, and shift the role of valuation from economic justification to legal protection. This paper contributes to a deeper understanding of the intersection between legal risk and financial valuation in corporate transactions